Drug Abuse and Implications on Students Learning: A Conceptual Review Emphasized on Sokoto, Nigeria - Aliyu, Samaila; Umar, Kabiru (EDUMALSYS Journal of Research in Education Management, 2024)
Drug abuse is a worldwide issue threatening almost all aspects of human life. The aim of this paper is to consider a review of concepts of drug abuse and effects on academic/education of learners with a particular emphasis on Sokoto. Drug is a substance that alters the body. Many people administer drugs just for euphoria without proper justification, a condition that is dubbed as drug abuse. Drug abuse is spurred by peers, curiosity, family, accessibility, work, stress and relations. However, effects of drug abuse are multifold, on a major part drug abuse affect health and onward cause poor learning. Most importantly, rehabilitation, religious, law implications, and other policies need to be embraced to deal with drug abuse. The following themes were engaged: drug and drug abuse concepts, classification, common drugs, cause, effects, prevention, etc.